Technology Entrepreneurship Project (ENT 600) : Sony Corporation / Mohamad Hakimi Jaafar - Jaafar, Mohamad Hakimi (2021)
This project is an attempt to know how the theories can be applied to a practical situation. As a student in UiTM Arau, it is a part of a learning for everybody to perform a case study project. So, for this purpose, I got the opportunity to do a research on company which manufactured the same product that I want to develop, which is SONY Corporation SONY Corporation is a Japanese multinational conglomerate corporation headquartered in Kōnan, Minato, and Tokyo. The company operates as one of the world's largest manufacturers of consumer and professional electronic products, the largest video game console company, the second largest video game publisher, the second largest record company, as well as one of the most comprehensive media companies, being the largest Japanese media conglomerate by size overtaking the privately held, family-owned Yomiuri Shimbun Holdings, the largest Japanese media conglomerate by revenue. One of their focused products is the SONY PlayStation series. In the first part of the study, I found that several problems that slowed down the business of SONY PlayStation. My focused is on PlayStation 4. Those problem are the low effectiveness of DualShock 4 controller and there is no wireless charging mode for the controller. At the end of the study, I performed a SWOT analysis to detect this kind of problems. I recommend SONY to produce an official Keyboard and mouse for PlayStation 4. I also recommend SONY to produce a wireless charging mode to charge the DS4 to make this product can give full satisfaction to their customers.